Traumatic colonic injuries in Westmead Hospital – A paradigm shift in management over 10 years. (October 2017) - Lorenzo, Aldenb; Pham, Helen; Zahid, Assad; Nguyen, Ba; Pathmanathan, Nimalan; Ctercteko, Graeme; Hsu, Jeremy M
: Over the years, there has been a shift towards more conservative treatment, with primary repair of colonic injuries being preferred over faecal diversion. We present a cohort study of the management of penetrating colon injury over the past 10 years from a major trauma hospital in western Sydney. We aim to evaluate the trend of operative management of penetrating colonic injuries. Methods: Patients were identified via the prospectively collected trauma registry at Westmead Hospital from 2003 to 2013. Fifty-seven patients initially identified with a proven diagnosis of penetrating colonic injury had their medical records reviewed. Excluded in the study are patients who had rectal injuries or serosal tears of the colon. Patient characteristics, mechanisms of injury, treatment course and complications were analysed. Extent of colonic injury was graded of using American Association for the Surgery of Trauma scalings. Results: A total of 55 patients were then included in the study. Primary repair of colon injuries was the most common method used (63.6%, n = 35) followed by resection and primary anastomosis (21.8% n = 12), diverting colostomy (14.3%, n = 5) and non-operative management (5.5%, n = 3). There was a higher rate of diversion in the earlier time period (2003–2007) when compared to the later time period (2008–2013), p = 0.03. Over the 10-year period, there was no significant difference with regards to complications among groups, particularly intra-abdominal complications. Conclusion: From 2003 to 2013, there is a shift of management of penetrating colonic injuries from diversion to resection and primary anastomosis to that of primary repair. Primary repair of colonic injuries is a safe option and is associated with low morbidity. It should be considered as a valid tool in the armamentarium of today's surgeon.